Licensing of Wood Treatment Pesticide Applicators in Florida - Frederick M. Fishel (EDIS)
PI-155, a 3-page fact sheet by Frederick M. Fishel, explains the licensing and regulation of persons who apply restricted use wood treatment pesticides in Florida. Published by the UF Pesticide Information Office, June 2007.